One health - eco-health - Rolston, Holmes, 1932-2025, speaker; Chan, Chang-Chuan, speaker; Chou, Kuei-Tien, speaker (Colorado State University. Libraries, 2016)
Lecture: One Health - Eco-Health given the at National Taiwan University, Risk Society and Policy Research Center, College of Social Science on June 8, 2016. There is only one world and only one health. Health effects ripple throughout the web of life. Human health requires thinking in ecological contexts, increasingly in more global ones. This further suggests more inclusive ethical concerns: global, international, and interspecific, beyond the immediate protection of human individuals from disease. Developed countries, which may have thought themselves protected with their high technologies and advanced medical systems, discover they are still linked with health, human and animal, in the developing world, even in wild nature, and vulnerable to disruptions there, to which they may also be contributing. Thinking of health must consider our entwined destiny with our landscapes. Ecology is strikingly like medical science. Both are therapeutic sciences. Ecologists are responsible for environmental health, which is really another form of public health. Health is just as much "skin-out" as it is "skin-in." It is hard to live a healthy life in a sick environment.
Lecture: One health - eco-health
Lecture given in English and translated in Mandarin.
To request a transcript, please contact library_digitaladmin@mail.colostate.edu or call (970) 491-1844.
Keywords: global health; world health; pandemics; domestic animals; wild animals; Nipa virus; SARS; avian flu; ebola; BSE; bovine spongiform encephalopathy; HIV/AIDS; Superfund; Deepwater Horizon; Zika virus; West Nile virus; Kepone